Mathematical modeling of magneto pulsatile blood flow through a porous medium with a heat source - Sharma, Bhupendra Kumar; Sharma, Madhu; Gaur, Rajarshi; Mishra, Abhishek (Zielona Góra: Uniwersytet Zielonogórski)
In the present study a mathematical model for the hydro-magnetic non-Newtonian blood flow in the non-Darcy porous medium with a heat source and Joule effect is proposed. A uniform magnetic field acts perpendicular to the porous surface. The governing non-linear partial differential equations have been solved numerically by applying the explicit finite difference Method (FDM). The effects of various parameters such as the Reynolds number, hydro-magnetic parameter, Forchheimer parameter, Darcian parameter, Prandtl number, Eckert number, heat source parameter, Schmidt number on the velocity, temperature and concentration have been examined with the help of graphs. The present study finds its applications in surgical operations, industrial material processing and various heat transfer operations.
Keywords: heat source; blood flow; porous medium; MHD